Kinetic pathways of solid–solid phase transitions dictated by short-range interactions - Hillary Pan; Julia Dshemuchadse (Proceedings of the National Academy of Sciences, 2025)
Structural phase transformations allow us to design materials from the ground up. Predicting the structural transformation of crystals during solid–solid phase transitions, however, is challenging, as the transition can proceed through multiple pathways that are difficult to probe experimentally. Using minimal computational models, we show that distinct kinetic pathways between body-centered cubic (bcc) and face-centered cubic (fcc) crystal structures can be encoded into a system by specific particle interactions. By investigating the dynamics of these transitions, we resolve three different pathways at a particle-by-particle level: a direct bcc-to-fcc transition, a transition involving an intermediate, long-lived body-centered tetragonal (bct) phase, and a microstructure-dependent transition pathway with a competing hexagonal close-packed (hcp) phase. These kinetic pathways are intrinsically linked to the shape of the underlying particle–particle interactions, suggesting routes for controlling the transformation pathways of soft matter systems. Furthermore, our investigations provide fundamental insights into solid–solid phase transition mechanisms generalizable across length scales.